(untitled) (Symposium on Natural and Applied Sciences, 2026)
Digital technologies have significantly transformed the process of language learning in the 21st century. The integration of online platforms, artificial intelligence, mobile applications, and multimedia tools has created new opportunities for learners and educators. This article analyzes the impact of digital transformation on language learning, focusing on technological innovations, teaching methodologies, and learner engagement. The study also discusses the advantages and challenges of digital language learning and highlights the role of digital tools in developing communicative competence. The findings suggest that digital technologies enhance accessibility, flexibility, and effectiveness in language education.